2018
DOI: 10.1038/s41467-018-06232-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability regulates topsoil carbon dynamics after permafrost thaw by altering microbial metabolic efficiency

Abstract: Input of labile carbon may accelerate the decomposition of existing soil organic matter (priming effect), with the priming intensity depending on changes in soil nitrogen availability after permafrost thaw. However, experimental evidence for the linkage between the priming effect and post-thaw nitrogen availability is unavailable. Here we test the hypothesis that elevated nitrogen availability after permafrost collapse inhibits the priming effect by increasing microbial metabolic efficiency based on a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(119 citation statements)
references
References 68 publications
5
109
0
Order By: Relevance
“…Meanwhile, the shift from anoxic to oxic conditions may also stimulate root growth of plant species that prefer soil aerobic conditions (Iversen et al, ). This deduction was confirmed by the increased root biomass in the top 15 cm, with an increment of approximately 12.1–40.7 g m − 2 along the thaw sequence (Chen et al, ). Taken together, the increased root metabolism and biomass may promote plant N uptake, such as uptake of small organic N forms (peptides, amino acids, etc.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Meanwhile, the shift from anoxic to oxic conditions may also stimulate root growth of plant species that prefer soil aerobic conditions (Iversen et al, ). This deduction was confirmed by the increased root biomass in the top 15 cm, with an increment of approximately 12.1–40.7 g m − 2 along the thaw sequence (Chen et al, ). Taken together, the increased root metabolism and biomass may promote plant N uptake, such as uptake of small organic N forms (peptides, amino acids, etc.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the MIM/GNM during the early thaw stage was similar to that in the control but increased during the middle and late thaw stages (Figure a), demonstrating that microbial N limitation became stronger along the thaw sequence. Such a pattern was supported by the increased stoichiometric imbalance between microorganisms and their resources (R C:N /B C:N ) after thermokarst formation (Chen et al, ), which also indicated enhanced microbial N limitation (Mooshammer et al, ). Moreover, the MIM/GNM was positively correlated with the R C:N /B C:N along this thaw sequence (Figure b).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, we found that the microbial metabolic quotient (qCO 2 ) was positively related to both R H ‐SOC new and RPE (Figure c). This suggests that an enhanced rhizodeposition by acquisitive species increase microbial allocation of energy to mineralization activities relative to growth (Shahzad et al, ), potentially in relation with a reduction in N availability by enhanced root N uptake, a lower carbon use efficiency and a faster turnover of microbial biomass (Chen et al, ; Sinsabaugh, Moorhead, Xu, & Litvak, ). This variation in microbial activity could also potentially be linked to the selection of rhizosphere microbiomes with contrasting SOC mineralization abilities by plant species with different economic strategies (Pascault et al, ; Schimel & Schaeffer, ).…”
Section: Discussionmentioning
confidence: 99%